2010
DOI: 10.1007/s11783-010-0254-6
|View full text |Cite
|
Sign up to set email alerts
|

Community dynamics of ammonia oxidizing bacteria in a full-scale wastewater treatment system with nitrification stability

Abstract: To determine whether the functional stability of nitrification was correlated to a stable community structure of ammonia oxidizing bacteria (AOB) in a fullscale wastewater treatment plant, the AOB community dynamics in a wastewater treatment system was monitored over one year. The community dynamics were investigated using specific PCR followed by terminal restriction fragment length polymorphism (T-RFLP) analysis of the amoA gene. The T-RFLP results indicated that during the period of nitrification stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The microbial ecology of the wastewater treatment plants has been studied elsewhere, using various molecular tools, viz. fluorescence in situ hybridisation (FISH; Egli et al, 2003), denaturing gradient gel electrophoresis (Stamper et al, 2003), terminal restriction fragment length polymorphism (T-RFLP; Wang et al, 2011) and clone library (Figuerola & Erijman, 2007). Each of these methods has its own limitations; however, in terms of performance, cost and read lengths, the 454-pyrosequencing technology stands out, because of its speed, cost-effectiveness and longer read length (c. 400 bp; Shendure & Ji, 2008).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The microbial ecology of the wastewater treatment plants has been studied elsewhere, using various molecular tools, viz. fluorescence in situ hybridisation (FISH; Egli et al, 2003), denaturing gradient gel electrophoresis (Stamper et al, 2003), terminal restriction fragment length polymorphism (T-RFLP; Wang et al, 2011) and clone library (Figuerola & Erijman, 2007). Each of these methods has its own limitations; however, in terms of performance, cost and read lengths, the 454-pyrosequencing technology stands out, because of its speed, cost-effectiveness and longer read length (c. 400 bp; Shendure & Ji, 2008).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…By enriching selected functional microorganisms in the activated sludge of wastewater treatment plant (WWTP), microbial activities in the sludge community are accelerated, enabling removal of oxygen-depleting organics, toxics, and nutrients. Biological WWTPs must be functionally stable to continuously and steadily remove contaminants which rely upon the activity of complex microbial communities [1] , [2] . Therefore, a better understanding of the microbial community structure and functional genes of activated sludge in WWTPs can help elucidate the mechanisms of biological pollutant removal and improve the treatment performance and operational stability [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Although some of the previous investigations targeted certain microorganisms in activated sludge systems based on functional genes, such as ammonia-oxidizing bacteria and archaea (AOB and AOA) (Whang et al 2009;Wang et al 2011Wang et al , 2012b, denitrifying bacteria (Srinandan et al 2011), and sulfur-oxidizing bacteria (SOB) (Luo et al 2011), to date, few studies profiling overall functional genes have been reported. As wastewater contains an array of organic compounds including a wide range of lipids, proteins, and carbohydrates, and inorganic materials like metals (Gray 2010), we expect that the composition of functional genes of activated sludge is complicated.…”
Section: Introductionmentioning
confidence: 99%